2019
DOI: 10.1016/j.ajogmf.2019.100053
|View full text |Cite
|
Sign up to set email alerts
|

Associations between unstable housing, obstetric outcomes, and perinatal health care utilization

Abstract: BACKGROUND: While there is a growing interest in addressing social determinants of health in clinical settings, there are limited data on the relationship between unstable housing and both obstetric outcomes and health care utilization. OBJECTIVE: The objective of the study was to investigate the relationship between unstable housing, obstetric outcomes, and health care utilization after birth. STUDY DESIGN: This was a retrospective cohort study. Data were drawn from a database of liveborn neonates linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
1
34
1
Order By: Relevance
“…22,28 Housing instability or homelessness was consistently associated with an increased odds of preterm birth in multiple studies, with increased adjusted odds ranging from 20% to 43%. 1,22,29,32 One study found no association, but this study had a limited sample size with less than 20 individuals in each group experiencing preterm birth and was rated very low GRADE and poor internal validity. 31 One study found that severe housing instability was associated with a 73% greater odds of low birthweight and/or preterm birth (aOR 1.73, 95% CI 1.28-2.32).…”
Section: Synthesis Of Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…22,28 Housing instability or homelessness was consistently associated with an increased odds of preterm birth in multiple studies, with increased adjusted odds ranging from 20% to 43%. 1,22,29,32 One study found no association, but this study had a limited sample size with less than 20 individuals in each group experiencing preterm birth and was rated very low GRADE and poor internal validity. 31 One study found that severe housing instability was associated with a 73% greater odds of low birthweight and/or preterm birth (aOR 1.73, 95% CI 1.28-2.32).…”
Section: Synthesis Of Resultsmentioning
confidence: 82%
“…The screening process yielded 14 studies meeting inclusion criteria (Figure 1). 1,2,[21][22][23][24][25][26][27][28][29][30][31][32] All studies were observational; studies were either retrospective cohort studies (n=10, 71.4%), cross-sectional observational studies (n=3, 21.4%), or prospective cohort studies (n=1, 7.1%). (Table 1)…”
Section: A Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Studies have also documented increased health care use and costs associated with housing instability, homelessness, or both. [11][12][13] Strategies to prevent homelessness and reduce housing instability may improve health and reduce avoidable health care use. 12 Innovative solutions that provide health and housing resources, commonly known as sup-portive housing, may be essential for improving population health.…”
Section: Housing Intervention For Medically Complex Families Associated With Improved Family Health: Pilot Randomized Trialmentioning
confidence: 99%